2020
DOI: 10.1088/1755-1315/539/1/012057
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of world LNG production capacity

Abstract: The article considers issues of global LNG production capacities. A brief description of the dynamics of global LNG trade is given and changing the structure of global energy consumption is considered. The analysis of the global dynamics of LNG production capacities is presented, as well as the regional structure of LNG capacities. Production capacities in the Asia-Pacific region, the Middle East, countries of Africa, America, as well as Russia and Norway are researched and analyzed in details. The paper also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Fulwood (2020) identifies the potential for smaller Asian markets to contribute significantly to LNG demand in the coming decades [13]. Additionally, Najm (2020) demonstrates the negative impact of renewable energy adoption on the LNG trade, emphasizing the importance of investing in cleaner energy technologies to reduce global LNG trade [11].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Fulwood (2020) identifies the potential for smaller Asian markets to contribute significantly to LNG demand in the coming decades [13]. Additionally, Najm (2020) demonstrates the negative impact of renewable energy adoption on the LNG trade, emphasizing the importance of investing in cleaner energy technologies to reduce global LNG trade [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In light of the growing demand for natural gas in emerging countries and its impact on global supply, the security of gas supply in Europe has become a paramount concern. The rapid growth of gas demand in emerging countries, such as China and India, presents a challenge to the stability of gas supply in Europe [11] as these countries increase their use of natural gas, competition for limited supplies of LNG intensifies, leading to potential price volatility and supply chain disruptions.…”
Section: Overview Of the Lng Global Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…As global oil reserves decline, global LNG production increases. In 2019, LNG production reached 419 million tons of LNG per annum (MTPA), with 37% in Asia-Pacific and 24% in the Middle East [12]. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As LNG must be subjected to the process of liquefaction, it is then purified from most contaminants, a step that is overlooked during pipeline transport. [5] Since the early 2000s, global LNG production capacities have increased by more than eight times [6]. Moreover, several studies have shown an upturn in the total gas trade [7][8][9], from 100 million tonnes in 2000 to 354.7 million tonnes in 2019.…”
Section: Introductionmentioning
confidence: 99%